IMPROVING FOURTH GRADE NATURAL SCIENCE LEARNING OUTCOMES WITH TYPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) COOPERATIVE MODEL - Irma Sari BR Purba (PrimaryEdu : Journal of Primary Education, 2018)
This study was conducted to determine the improvement of fourth grade  science learning outcomes using the STAD type cooperative model. The subjects were all students in fourth grade 046573 Berastagi, Karo. The object of the research is the improvement of the fourth grade science learning outcomes using the STAD type cooperative model. The research instrument used was the observation sheet and multiple-choice tests. Data analysis used is individual learning outcomes, classical completeness, and average student learning outcomes. From the analysis of the data obtained from observations the implementation of learning activities of teachers increased 12.11% from a value of 59% to 71.1%, student activity increased from a score of 62 to 74, the completeness of individuals who expressed achieving KKM scores of 65, classical completeness increased from 66.67% to 87.50 %, and the average value increased from 64.58 to 76.25. From the results of the study it can be concluded that the implementation of learning in good category and student learning outcomes increase after using the STAD type cooperative learning model in science lessons. Keywords: Learning outcomes, student team achievement division learning